Analisis Fiqh Siyasah dalam Pembentukan Peraturan tentang Trading in Influence di Indonesia - Rahayu, Fadilah Qotimatun Puji; Fatmah, Fatmah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2024)
This research explains the important role of mosques in maintaining the mental health of generation Z in the digital era. Generation Z faces social and technological changes that affect their mental health. Mosques, as religious and community centers, can provide useful social support, religious values ​​and spiritual empowerment. This research focuses on West Nusa Tenggara, a region with strong cultural and religious traditions, while considering the impact of social and technological transformation. Through a literature review, we explore the role of mosques in generation Z's mental health, exploring local culture, social norms, and challenges and opportunities in an increasingly digitally connected society. It is hoped that the research results will provide guidance for local governments, mosque communities and related organizations in developing specific mental health programs, interventions and policies for Generation Z in West Nusa Tenggara. With a deeper understanding of the factors that influence the role of mosques, this research contributes to ongoing efforts to improve the mental health of generation Z in the future.. Keywords: Mosque, Mental Health, Generation Z, West Nusa Tenggara, Literature Research.